The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s43046-020-00057-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Monte-Carlo algorithm in comparison with collapse-cone dose calculation algorithm of a commercial treatment planning system in the presence of high-density metallic implant: a dosimetric study

Abstract: Background The number of people with implanted hip prosthesis has grown worldwide. For radiotherapy planning of patients with hip implants, few main challenges are encountered. The aim of the present study was to evaluate the feasibility of different planning algorithms in the presence of high-density metallic implant in the treatment of patients with carcinoma cervix. Results It was found that D98% were 44.49 ± 0.11, 44.51 ± 0.13, 44.39 ± 0.22, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…This may be attributed to the differences in the dose-calculation models, the uncertainty of film dosimetry, and simplifications assumed by TPS-MC simulations in terms of physical processes [ 19 , 24 ]. Certain reports on dose calculations in TPSs have shown that they can be performed accurately, including around high-Z materials [ 25 , 26 ]. However, these reports were based on large-volume high-Z materials and not on extremely small high-Z materials, such as the seeds used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the differences in the dose-calculation models, the uncertainty of film dosimetry, and simplifications assumed by TPS-MC simulations in terms of physical processes [ 19 , 24 ]. Certain reports on dose calculations in TPSs have shown that they can be performed accurately, including around high-Z materials [ 25 , 26 ]. However, these reports were based on large-volume high-Z materials and not on extremely small high-Z materials, such as the seeds used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The material used for was “titanium”(composition: titanium 88.5%–91.0%; aluminum 5.6%–6.5%, vanadium 3.5%–4.5%, iron 0.25%, oxygen 0.13% and carbon 0.08%, average ED 3.74 relative to water; diameter of femoral heads of prosthesis ranging from 40 to 54 mm. [ 20 ] The thermoplastic cast was made for every patient. The acquired images were transferred to Varian Soma vision contouring stations.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%